Identifikasi Kurikulum dan Sarana Prasarana Melalui Analisis SWOT Dalam Upaya Peningkatan Mutu Pembelajaran di MI Sekolah Alam - Yayah Khoeriyah (Universitas Islam Bunga Bangsa Cirebon, 2021)
Abstrak Analisis SWOT menurut kamus besar bahasa indonesia adalah suatu proses pemecahan masalah yang dimulai dengan dugaan akan kebenarannya dan dapat juga diartikan sebagai pengkajian terhadap suatu peristiwa (tindakan, hasil pemikiran dan sebagainya) untuk mengetahui keadaan yang sebenarnya. Kata SWOT sendiri merupakan kependekan dari beberapa uraian kata yaitu: strenghts (kekuatan), weakness (kelemahan), opportunity (peluang) dan threats (tantangan). Salah satu dari sekian banyaknya permasalahan pendidikan yang dihadapi oleh bangsa indonesia saat ini adalah mengenai rendahnya mutu pendidikan indonesia di setiap jenjang dan satuan pendidikan yang ada, khususnya pada tingkatan pendidikan dasar dan menengah. Penelitian ini bertujuan untuk mengetahui identifikasi kurikulum dan sarana prasana dengan menggunakan analisis SWOT dalam upaya meningkatkan mutu pendidikan di Madrasah Ibtidaiyah sekolah alam indramayu, melalui analisis SWOT ini akan membantu Madrasah Ibtidaiyah sekolah alam Indramayu mengetahui mengenai kekuatan dan kelemahan yang dimiliki Madrasahsah Ibtidaiyah sekolah alam Indramayu. Terutama pada faktor internal sekolah yakni kurikulum dan sarana prasarana sebagai upaya untuk meningkatkan mutu pendidikan di Madrasah Ibtidaiyah sekolah alam Indramayu. Penelitian ini merupakan penelitian kualitatif yang bermaksud untuk memahami fenomena tentang apa yang di alami oleh subjek penelitian. Dalam penelitian ini yang menjadi sumber data adalah seluruh stakeholder atau seluruh pihak sekolah Madrasah Ibtidaiyah sekolah alam Indramayu. Pengumpulan data dilakukan dengan teknik wawancara dan observasi lapangan sebagi penguat atas teori yang telah dijabarkan. Selanjutnya data yang sudah terkumpul akan diolah dengan triangulasi data yaitu dengan mereduksi data, display data dan verifikasi untuk kesimpulan data. Hasil penelitian dari identifikasi kurikulum dan sarana prasarana dengan menggunakan analisis SWOT untuk meningkatkan mutu pendidikan di Madrasah Ibtidaiyah sekolah alam Indramayu sudah menunjukkan adanya hasil yang cukup memuaskan dalam peningkatan mutu pendidikan yang ada di Madrasah Ibtidaiyah sekolah alam indramayu tersebut. SWOT analysis according to the large Indonesian dictionary is a problem-solving process that begins with an assumption of its truth and can also be interpreted as an assessment of an event (action, results of thoughts, etc.) to find out the real situation. The word SWOT itself is an abbreviation of several word descriptions, namely: strengths, weaknesses, opportunities and threats. One of the many educational problems faced by the Indonesian nation today is the low quality of Indonesian education at every level and existing education unit, especially at the primary and secondary education levels. This study aims to determine the identification of the curriculum and infrastructure using SWOT analysis in an effort to improve the quality of education in Madrasah Ibtidaiyah, Indramayu Natural School, through this SWOT analysis will help Madrasah Ibtidaiyah, Indramayu Natural School, to know about the strengths and weaknesses of Madrasahsah Ibtidaiyah, Indramayu Natural School. Especially in the school's internal factors, namely the curriculum and infrastructure as an effort to improve the quality of education at Madrasah Ibtidaiyah, Indramayu natural school. This research is a qualitative research which intends to understand the phenomena experienced by the research subjects. In this study, the data sources were all stakeholders or all parties in the Madrasah Ibtidaiyah school, Indramayu Nature School. Data collection was carried out by interviewing techniques and field observations as reinforcement of the theory that has been described. Furthermore, the data that has been collected will be processed with data triangulation, namely by reducing data, displaying data and verification for data conclusions. The research results from the identification of curriculum and infrastructure using SWOT analysis to improve the quality of education at Madrasah Ibtidaiyah, Indramayu natural school, have shown satisfactory results in improving the quality of education in Madrasah Ibtidaiyah, Indramayu natural school. abbreviation of several word descriptions, namely: strengths, weaknesses, opportunities and threats. One of the many educational problems faced by the Indonesian nation today is the low quality of Indonesian education at every level and existing education unit, especially at the primary and secondary education levels. This study aims to determine the identification of the curriculum and infrastructure using SWOT analysis in an effort to improve the quality of education in Madrasah Ibtidaiyah, Indramayu Natural School, through this SWOT analysis will help Madrasah Ibtidaiyah, Indramayu Natural School, to know about the strengths and weaknesses of Madrasahsah Ibtidaiyah, Indramayu Natural School. Especially in the school's internal factors, namely the curriculum and infrastructure as an effort to improve the quality of education at Madrasah Ibtidaiyah, Indramayu natural school. This research is a qualitative research which intends to understand the phenomena experienced by the research subjects. In this study, the data sources were all stakeholders or all parties in the Madrasah Ibtidaiyah school, Indramayu Nature School. Data collection was carried out by interviewing techniques and field observations as reinforcement of the theory that has been described. Furthermore, the data that has been collected will be processed with data triangulation, namely by reducing data, displaying data and verification for data conclusions. The research results from the identification of curriculum and infrastructure using SWOT analysis to improve the quality of education at Madrasah Ibtidaiyah, Indramayu natural school, have shown satisfactory results in improving the quality of education in Madrasah Ibtidaiyah, Indramayu natural school.